2021
DOI: 10.1021/acsmaterialsau.1c00009
|View full text |Cite
|
Sign up to set email alerts
|

(NH4)2AgX3 (X = Br, I): 1D Silver Halides with Broadband White Light Emission and Improved Stability

Abstract: Recently, ternary copper­(I) halides have emerged as alternatives to lead halide perovskites for light emission applications. Despite their high-efficiency photoluminescence (PL) properties, most copper­(I) halides are blue emitters with unusually poor tunability of their PL properties. Here, we report the impact of substitution of copper with silver in the high-efficiency blue-emitting Cu­(I) halides through hydrothermal synthesis and characterization of (NH4)2AgX3 (X = Br, I). (NH4)2AgX3 are found to exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
(130 reference statements)
2
34
0
Order By: Relevance
“…[43] This emission mechanism is also supported by the literature precedent of analogous ternary silver halides. [52] As another supporting evidence for the significant role of defects in determining the photophysical properties of A 2 AgX 3 , previously it was reported that the pulling of vacuum on a Rb 2 AgBr 3 sample significantly increases the intensity of the defect PL peak. [43] To test this further, we prepared Rb 2 AgI 3 using two differing techniques: (i) the more reliable method of sample preparation involved annealing of the sample in a vacuum sealed ampoule under 5 mTorr for 80 h, followed by regrinding and reannealing for another 80 h. The second method involved only a short annealing time of 12 h. The PL spectra for resultant samples are starkly different (Figure S11, Supporting Information), suggesting the dominant STE emission for the second sample with short annealing time.…”
Section: Resultsmentioning
confidence: 71%
“…[43] This emission mechanism is also supported by the literature precedent of analogous ternary silver halides. [52] As another supporting evidence for the significant role of defects in determining the photophysical properties of A 2 AgX 3 , previously it was reported that the pulling of vacuum on a Rb 2 AgBr 3 sample significantly increases the intensity of the defect PL peak. [43] To test this further, we prepared Rb 2 AgI 3 using two differing techniques: (i) the more reliable method of sample preparation involved annealing of the sample in a vacuum sealed ampoule under 5 mTorr for 80 h, followed by regrinding and reannealing for another 80 h. The second method involved only a short annealing time of 12 h. The PL spectra for resultant samples are starkly different (Figure S11, Supporting Information), suggesting the dominant STE emission for the second sample with short annealing time.…”
Section: Resultsmentioning
confidence: 71%
“…For the latter, since the mechanism of degradation involves oxidation of Cu­(I) to Cu­(II), a direct replacement of copper with silver can be considered. This has been demonstrated by the preparation and characterization of the Ag analogues of the “213” copper halides, A 2 AgX 3 (A = Rb, Cs, NH 4 ; X = Cl, Br, I). , Note that not all of A 2 AgX 3 are isostructural to A 2 CuX 3 ; while Cs 2 AgX 3 adopts the K 2 CuCl 3 type structure and are isostructural to A 2 CuX 3 , the use of smaller A + cations in Rb 2 AgX 3 , (NH 4 ) 2 AgX 3 , and K 2 AgX 3 leads to the K 2 AgI 3 type structure (Figure ). Both structure types are largely similar and feature 1 ∞ [AgX 3 ] 2– chains separated by the A + cations.…”
Section: All-inorganic Copper Halidesmentioning
confidence: 99%
“…Among the potential practical benefits of exploring low‐dimensional metal halides is that they typically exhibit much enhanced excitonic properties thanks to confinement effects. Consequently, many low‐dimensional metal halides, particularly 0D halides, have been reported to exhibit high‐efficiency broadband photoluminescence (PL) properties due to the recombination of self‐trapped excitons (STEs) at room temperature [8–10,13–22] . Some notable examples include white‐light emitters based on 0D lead halides with photoluminescence quantum yield (PLQY) values up to 45 %, [10,13–14] and tunable broadband emission with PLQYs up to 89 % from 0D Sb(III) halides [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many low-dimensional metal halides, particularly 0D halides, have been reported to exhibit high-efficiency broadband photoluminescence (PL) properties due to the recombination of self-trapped excitons (STEs) at room temperature. [8][9][10][13][14][15][16][17][18][19][20][21][22] Some notable examples include whitelight emitters based on 0D lead halides with photoluminescence quantum yield (PLQY) values up to 45 %, [10,[13][14] and tunable broadband emission with PLQYs up to 89 % from 0D Sb(III) halides. [15] Depending on the choices of the organic cation A, B metal cation, and X halide anion, the band gaps of the inorganic anions and HOMO-LUMO gaps of the organic cations can be independently tuned to obtain low-dimensional materials in which PL controllably originates from the organic and inorganic units, or a simultaneous PL emission from both components.…”
Section: Introductionmentioning
confidence: 99%